Perancangan Dan Implementasi Pembagian Bandwidth Menggunakan Mikrotik Di PT. Satria Jaya Prima (2023) - Siti Rere Okta Dinda; Hastha Sunardi; Zulkifli (Universitas Indo Global Mandiri, 2023)
The increasing demand and use of internet networks at PT. Satria Jaya Prima to access a website-based sales system, the more user demand for problems that occur on user devices such as unstable internet networks. Currently the use of internet network at PT. Satria Jaya Prima has not been efficient because there is no balanced bandwidth regulation, thus making the internet network capacity usage gap and making the internet network unstable. Based on these problems, research is needed that can be applied to overcome these problems, namely managing bandwidth using Mikrotik. In the network, a device is needed that can manage the existing internet network. This device is called Mikrotik RouterBoard. Routers that will be used in the internet network of PT. Satria Jaya Prima runs with Mikrotik OS for bandwidth and user management and manages the existing internet network according to the internet needs of internet network users. In this study, Mikrotik is configured using Winbox using the Simple Queue Peer Connection Queue (PCQ) method, with bandwidth management and users using the Mikrotik Router, the internet network connection will be smoother, because the existing bandwidth is allocated to each user based on the bandwidth needs needed by each internet network user